Can intercropping with the world's three major beverage plants help improve the water use of rubber trees?. Issue 6 (12th July 2016) - Wu, Junen; Liu, Wenjie; Chen, Chunfeng
Summary: The dramatic expansion of rubber plantations in mainland South‐East Asia and south‐west China has caused many eco‐environmental problems, especially negative hydrological consequences. These problems have gradually worsened and pose formidable threats to rubber agriculture, especially in the light of increasingly frequent extreme weather events. Although rubber‐based agroforestry systems are regarded as the best solution for improving the sustainability of rubber agriculture and environmental conservation, plant water use and related interactions have rarely been examined in such systems. We primarily used stable isotope (δD, δ 18 O and δ 13 C) methods to test whether intercropping could improve the water use and extreme weather tolerance (extreme cold and drought in our study) of rubber trees in three types of promising agroforestry systems (i.e. rubber with tea, coffee and cocoa) in Xishuangbanna, China. We found that the rubber tree is a drought‐avoidance plant with strong plasticity with respect to water uptake. This characteristic is reflected by its ability to cope with serious seasonal drought, allowing it to avoid interspecific competition for water. The rubber trees showed wasteful water behaviour unless they were intercropped with tea or coffee. However, these intercropped species exhibited drought‐tolerance strategies and maintained lower water use efficiencies to strengthen their competitive capacity for surface soil water. The stable δ 13 C values of the intercrop leaves indicated that all the agroforestry systems have stable internal microclimatic environments or higher resistance. Synthesis and applications . This study suggests that interspecific competition for water can enhance the water use efficiency of drought‐avoidance plants (i.e. rubber trees) and lead to complementarity between the root distributions of plants in rubber agroforestry systems (i.e. rubber with tea, coffee and cocoa). All agroforestry systems have higher resistance, but tea was the most suitable intercrop in terms of water use because the interspecific competition for water was moderate and the agroforestry system retained much more soil water and improved the water use efficiency of the rubber tree. Considering the root characteristics of the tea trees, we suggest that the crops selected for intercropping with rubber trees should have a relatively fixed water use pattern, short lateral roots and a moderate amount of fine roots that overlap with the roots of the rubber trees in the shallow soil layer. Abstract : This study suggests that interspecific competition for water can enhance the water use efficiency of drought‐avoidance plants (i.e. rubber trees) and lead to complementarity between the root distributions of plants in rubber agroforestry systems (i.e. rubber with tea, coffee and cocoa). All agroforestry systems have higher resistance, but tea was the most suitable intercrop in terms of water use because the interspecific competition for water was moderate and the agroforestry system retained much more soil water and improved the water use efficiency of the rubber tree. Considering the root characteristics of the tea trees, we suggest that the crops selected for intercropping with rubber trees should have a relatively fixed water use pattern, short lateral roots and a moderate amount of fine roots that overlap with the roots of the rubber trees in the shallow soil layer.